Guest editorial – are libraries privileged spaces? - Cox, Andrew M.; O'Neill, Anna; Wales, Tim (Taylor & Francis, 2025)
Introduction: A recently published book entitled ‘Privileged Spaces’ (Everitt & Everitt, Citation2024), explores how evolving university estates strategies impact library spaces. These so-called privileged library spaces provide ‘a haven to think, explore the wonders of rich collections, seek solace or simply meet friends’, but we wanted to take the opportunity in this editorial to explore where there are other definitions or tests of privilege which could equally be applied to the academic library.
Keywords: 4610 Library and information studies